Effects of dietary supplementation with alkaline mineral complex on in vitro ruminal fermentation and bacterial composition - Liu, Siyuan; Xie, Biao; Ji, Hongjin; Li, Shengli (Frontiers in Veterinary Science, 2024)
Dairy industry growth faces challenges in China due to inadequate forage, leading to high-concentrate diets and potential rumen issues. Buffering agents, like sodium bicarbonate, play a crucial role in stabilizing rumen pH. Alkaline Mineral Complex (AMC), a liquid additive with a pH of 14, shows promise in supporting dairy cow health and mitigating heat stress through ionization. This experiment was aimed to study the effect of adding AMC to total mixed ration (TMR) on in vitro ruminal fermentation and bacterial composition. AMCat 1, 2, 4 and 8 mL/kg was added to the substrate (0.5 g TMR). Nutrient digestibility was measured after 48 h fermentation, and fermentation parameters and microbial composition were measured after 48 h fermentation.The results of the experiment indicated that: The different concentrations of AMC showed a significant impact on time taken for gas production to reach 1/2 of the total gas production (HT) parameters (p < 0.05). Linear pH increase occurs at 6 and 24 hours with rising AMC concentration (p < 0.05), showing a quadratic trend at 12 hours (p < 0.05). The optimal buffering effect on rumen acid-base balance was